On the 3rd person marking in the Lithuanian verb system - Bammesberger, Alfred (Baltistica, 2017)
A specific feature of the verb in the Baltic languages is the same 3rd person singular, dual, and plural form. The prevailing opinion that Lith. vẽda reflects the inherited and later generalised 3 sg. form is questionable because Lith. vẽda can hardly be derived from the thematic paradigm of the protolanguage. The so-called semi-thematic -ē- and -ā- stems are frequently used in both the present and the past tense forms in the Baltic languages. In their 3 pl. forms the long vowel should have been shortened before the nasal consonant, however, due to paradigmic levelling the forms with -ē-n and -ā-n could have been restored. Since word-final combinations -ē- + n and -ā- + n did not usually occur, -n dropped out and the 3 sg. and 3 pl. forms merged. The thematic paradigm was later rearranged according to the pattern of semi-thematic conjugation.
Keywords: Lithuanian; historical morphology; verb